Crucial roles of mixed‐lineage leukemia 3 and 4 as epigenetic switches of the hepatic circadian clock controlling bile acid homeostasis in mice. Issue 3 (28th January 2015) - Kim, Dae‐Hwan; Rhee, Jennifer Chiyeon; Yeo, Sujeong; Shen, Rongkun; Lee, Soo‐Kyung; Lee, Jae W.; Lee, Seunghee
Abstract : The histone H3‐lysine‐4 methyltransferase mixed‐lineage leukemia 3 (MLL3) and its closest homolog, MLL4 (aka KMT2D), belong to two homologous transcriptional coactivator complexes, named MLL3 and MLL4 complexes, respectively. MLL3 plays crucial roles in multiple metabolic processes. However, the physiological roles of MLL4 in metabolism and the relationship between MLL3 and MLL4 in metabolic gene regulation are unclear. To address these issues, we analyzed the phenotypes of newly generated MLL4 mutant mice, along with MLL3 mutant and MLL3;MLL4 compound mutant mice. We also performed comparative genome‐wide transcriptome analyses in livers of MLL3, MLL4, and MLL3;MLL4 mutant mice. These analyses revealed that MLL3 and MLL4 complexes are key epigenetic regulators of common metabolic processes and the hepatic circadian clock. Subsequent mechanistic analyses uncovered that MLL3/4 complexes function as pivotal coactivators of the circadian transcription factors (TFs), retinoid‐related orphan receptor (ROR)‐α and ‐γ, in the hepatic circadian clock. Consistent with disturbed hepatic clock gene expression in MLL4 mutant mice, we found that rhythmic fluctuation of hepatic and serum bile acid (BA) levels over the circadian cycle is abolished in MLL4 mutant mice. Our analyses also demonstrate that MLL4 primarily impinges on hepatic BA production among several regulatory pathways to control BA homeostasis. Together, our results provide strong in vivo support for important roles of both MLL3 and MLL4 in similar metabolic pathways. Conclusion : Both MLL3 and MLL4 complexes act as major epigenetic regulators of diverse metabolic processes (including circadian control of bile acid homeostasis) and as critical transcriptional coactivators of the circadian TFs, RORs. (Hepatology 2015;61:1012–1023)